Illuminating CO2 reduction on frustrated Lewis pair surfaces: investigating the role of surface hydroxides and oxygen vacancies on nanocrystalline In2O3−x(OH)y1. Issue 22 (14th June 2015) - Ghuman, Kulbir Kaur; Wood, Thomas E.; Hoch, Laura B.; Mims, Charles A.; Ozin, Geoffrey A.; Singh, Chandra Veer
<x xml:space="preserve">Abstract</x> Designing catalytic nanostructures that can convert gaseous CO2 into carbon based fuels is a significant challenge, which requires a keen understanding of the chemistry of reactants, intermediates and products on surfaces.